1981
DOI: 10.1007/bf02396873
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature thermomechanical treatment on the mechanical properties of vanadium – modified AISI 4330 steel

Abstract: The relationships between the recovery and recrystallization of hot-deformed austenite grains and the precipitation of carbide on tempering in a 0.3C-Ni-Cr-Mo-V steel have been studied to examine closely the favourable effects of high-temperature thermomechanical treatment (HTMT) on the mechanical properties in steel. The results show that the strength and toughness increase with increasing degree of deformation by HTMT, particularly in which the ductile-brittle transition temperature as a measure of toughness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Another reason is relative to activating of carbides precipitation. References have proved that in this steel some carbide such as NC, VC, TiC can be formed (Easterling and Porter, 1992) and that these carbides inhibit the migration of grain boundaries (Bandyopadhyay et al, 1985;Lee and Chun, 1981). Thus, grains do not grow until dissolving carbides.…”
Section: Average Grain Sizes In Ccct Curvesmentioning
confidence: 93%
See 1 more Smart Citation
“…Another reason is relative to activating of carbides precipitation. References have proved that in this steel some carbide such as NC, VC, TiC can be formed (Easterling and Porter, 1992) and that these carbides inhibit the migration of grain boundaries (Bandyopadhyay et al, 1985;Lee and Chun, 1981). Thus, grains do not grow until dissolving carbides.…”
Section: Average Grain Sizes In Ccct Curvesmentioning
confidence: 93%
“…Consequently, these precipitates do not cause coarsening austenite grains to high temperatures and do not allow reducing the strength of steel. Furthermore, it has been proved that deformation causes increasing of carbide and nitride precipitation (Lee and Chun, 1981;Liu et al, 2000). This is the reason that this steel is in the group of highstrength steels.…”
Section: Precipitation In Nicrmov Steel and The Effect Of Deformationmentioning
confidence: 98%
“…9) Alone or in combination, all these factors can affect grain cohesion, and thus, the material toughness and are significantly dependent on hot working parameters. 9) On the other hand, it has been reported that the crack growth resistance of AISI 4330 steel is improved by the formation of metastable microstructures such as upper and lower bainite, 4,5) which is also dependent on the selection of high temperature processing parameters. Hence, a better understanding of the mechanisms governing microstructure evolution during open-die forging of these alloys would allow the optimum design of the thermomechanical process, and could help in developing suitable microstructures and minimize or avoid the observed cracking.…”
Section: Hot Deformation Behavior Of a Nickel-modified Aisi 4330 Steelmentioning
confidence: 99%
“…[2][3][4][5] In recent years, its applications in critical equipment used in the oil and gas industry have been on the rise. However, for certain specific applications, lower ductile-brittle transition temperatures or higher strength and wear resistance are required which can't be achieved with conventional AISI 4330 steel.…”
Section: Introductionmentioning
confidence: 99%